Anti‐Corruption Watchdog Accountability: The Limitations of Judicial Review's Ability to Guard the Guardians. Issue 3 (25th January 2016) - Howe, Sarah Withnall; Haigh, Yvonne
Abstract : Anti‐corruption watchdogs form an important part of integrity measures in Australia's system of government. Integrity theory places anti‐corruption watchdogs in a fourth branch of government and as a part of a national integrity system as a way of understanding how they detect and prevent corruption and promote integrity. Integrity theory claims that an important part of the oversight of watchdogs occurs through judicial review of watchdog decisions by the courts. However, it fails to recognise the unique limitations when undertaking judicial review of watchdog decisions. This article submits that it is important to recognise these limitations to properly assess the effectiveness of a national integrity system and a fourth branch of government. The article explores the unique limitations of the court's ability to hold watchdogs to account and offers suggestions for managing these limitations. Abstract : This article examines the limitation of judicial review in providing accountability to anti‐corruption watchdogs. It submits the effects of these limitations are not properly recognised by fourth branch integrity theory or national integrity system theory. It concludes it is not sufficient to claim the judiciary is the answer to the question 'who shall guard the guardians?'